The dog-faced water snakes, a revision of the genus Cerberus Cuvier, (Squamata, Serpentes, Homalopsidae), with the description of a new species - Murphy, John C.; Voris, Harold K.; Karns, Daryl R. (Zootaxa, 2012)
Snakes of the genus Cerberus Cuvier, 1829 occupy a unique, widespread coastal distribution and have a salt-tolerant physiology that allows members of the genus to move across a wide range of salinities from full salt water to freshwater. Cerberus nomenclature is revised based upon morphology and builds on previous molecular studies. Three species have been recognized by recent workers, here we recognize five species: the South Asian C. rynchops (Schneider 1799); the Southeast Asian-Philippine C. schneiderii (Schlegel 1837), a new combination; the freshwater Philippine endemic C. microlepis Boulenger 1896; the Australopapuan C. australis (Gray 1842); and a new species from Micronesia. We also select a lectotype for Homalopsis schneiderii Schlegel based upon a figure published in 1837 and restrict the type locality for this species to Timor. Evidence is also presented for a population of Cerberus australis in Indonesia, west of Weber’s Line.